A mouse ocular explant model that enables the study of living optic nerve head events after acute and chronic intraocular pressure elevation: Focusing on retinal ganglion cell axons and mitochondria. (July 2017) - Kimball, Elizabeth C.; Pease, Mary E.; Steinhart, Matthew R.; Oglesby, Ericka N.; Pitha, Ian; Nguyen, Cathy; Quigley, Harry A.
Abstract: We developed an explant model of the mouse eye and optic nerve that facilitates the study of retinal ganglion cell axons and mitochondria in the living optic nerve head (ONH) in an ex vivo environment. Two transgenic mouse strains were used, one expressing yellow fluorescent protein in selected axons and a second strain expressing cyan fluorescent protein in all mitochondria. We viewed an explanted mouse eye and optic nerve by laser scanning microscopy at and behind the ONH, the site of glaucoma injury. Explants from previously untreated mice were studied with the intraocular pressure (IOP) set artificially at normal or elevated levels for several hours. Explants were also studied from eyes that had undergone chronic IOP elevation from 14 h to 6 weeks prior to ex vivo study. Image analysis in static images and video of individual mitochondria or axonal structure determined effects of acute and chronic IOP elevation. At normal IOP, fluorescent axonal structure was stable for up to 3 h under ex vivo conditions. After chronic IOP elevation, axonal integrity index values indicated fragmentation of axon structure in the ONH. In mice with fluorescent mitochondria, the normal density decreased with distance behind the ONH by 45% (p = 0.002, t -test). Density increased with prior chronic IOP elevation to 21, 300 ± 4176 mitochondria/mm 2 compared to control 16, 110 ± 3159 mitochondria/mm 2 (p = 0.025, t -test), but did not increase significantly after 4 h, acute IOP elevation (1.5% decrease in density, p = 0.83, t -test). Mean normal mitochondrial length of 2.3 ± 1.4 μm became 13% smaller after 4 h of IOP elevation ex vivo compared to baseline (p = 0.015, t -test, N-10). Normal mitochondrial speed of movement was significantly slower in the anterograde direction (towards the brain) than retrograde, but there were more mitochondria in motion and traveling longer lengths in anterograde direction. The percent of mitochondria in motion decreased by >50% with acute IOP increase to 30 mm Hg after 60 min. A new ocular explant model implemented with eyes from transgenic mice with fluorescent cellular components provided real time measurement of the early events in experimental glaucoma and quantitative outcomes for neuroprotection therapy experiments. Highlights: An explant model of the mouse eye was developed in the living optic nerve head, the site of glaucoma injury. This model will facilitate the study of retinal ganglion cell axons (RGC) and mitochondria via laser scanning microscopy. Two transgenic mouse strains; one fluorescing selected RGC and another all mitochondria were imaged. Glaucoma bead model increase mitochondria density, but decrease in mitochondrial length & mitochondrial movement. Glaucoma caused fragmentation of axon structures at the ONH, increasing in severity with longer periods of glaucoma exposure.